1995
DOI: 10.1200/jco.1995.13.11.2769
|View full text |Cite
|
Sign up to set email alerts
|

Low specificity of cytokeratin 19 reverse transcriptase-polymerase chain reaction analyses for detection of hematogenous lung cancer dissemination.

Abstract: Contrary to prior reports, RT-PCR may detect non-tissue-specific constitutive low-level (illegitimate) expression of CK-19 mRNA in peripheral-blood mononuclear (PBMN) cells in a significant number of healthy controls. This finding may not only hamper the use of this assay system in lung cancer patients, but also questions its proposed applicability in patients with other epithelial tumors such as breast and prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
77
3
6

Year Published

1997
1997
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(90 citation statements)
references
References 19 publications
4
77
3
6
Order By: Relevance
“…For example, PGP-9.5 (Norris et al, 1994), prostate-specific antigen , cytokeratin 19 (Krismann et al, 1995) and tyrosinase transcripts (Foss et al, 1995) can be amplified from peripheral blood of healthy volunteers. Illegitimate transcription of EGP2 may also be the explanation of the positive results obtained by us in bone marrow and peripheral stem cell harvests of patients suffering from various haematological malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, PGP-9.5 (Norris et al, 1994), prostate-specific antigen , cytokeratin 19 (Krismann et al, 1995) and tyrosinase transcripts (Foss et al, 1995) can be amplified from peripheral blood of healthy volunteers. Illegitimate transcription of EGP2 may also be the explanation of the positive results obtained by us in bone marrow and peripheral stem cell harvests of patients suffering from various haematological malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…The main problem of RNA-based assays continues to be the almost universally present background signal (Traweek et al, 1993;Datta et al, 1994;Burchill et al, 1995;Krismann et al, 1995;Fields et al, 1996;Moscinski et al, 1996;Mapara et al, 1997;Zippelius et al, 1997). We have recently developed a method that overcomes these problems by making use of two relatively recent developments.…”
mentioning
confidence: 99%
“…14 However, it has been demonstrated that PCR-based techniques are prone to false positive results and thus of limited value for detection of haematogenous epithelial cancer dissemination. 15,16 Controversial results have been also reported in non-epithelial solid tumours. 17,18 We have developed a highly specific, less time consuming and technically simpler RT-PCR assay capable of detecting epithelial cells that would otherwise go undetected by presently available ICC methods.…”
mentioning
confidence: 99%